Video games for the assessment and treatment of attention-deficit/hyperactivity disorder: a systematic review. - Peñuelas-Calvo, Inmaculada; Jiang-Lin, Lin Ke; Girela-Serrano, Braulio; Delgado-Gomez, David; Navarro-Jimenez, Rocio; Baca-Garcia, Enrique; Porras-Segovia, Alejandro (European Child & Adolescent Psychiatry, 2022)
Attention-deficit/hyperactivity disorder (ADHD) is a prevalent and serious disorder among children. Video games have shown potential for aiding in child healthcare. Video games could contribute to the assessment and management of ADHD, but there are no previous reviews on this topic. Here, we systematically review the evidence about video game-based assessment tools and interventions for children diagnosed with ADHD. This review followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. The review protocol was registered in PROSPERO database. We searched four databases—PubMed, PsycInfo, Embase and clinicaltrials.gov—to identify original studies exploring either video game-based interventions or video game-based assessment tools in children with ADHD. After initial screening, full text revision and study selection, 22 articles were finally included in the review. Most studies used PC as platform, with a minority using a video console, pad, or 3D device. Video game-based assessment tools were generally effective in discriminating ADHD cases from controls, and in discriminating between ADHD subtypes. Video game-based therapeutic interventions were well accepted and generally effective in improving cognitive areas and decreasing ADHD symptoms. Gamification and cognitive training could be the main mechanisms underlying the usefulness and effectiveness of video game-based assessment tools and interventions. Software optimization and greater collaboration between developers and healthcare professionals are some of the priorities for future research in this area.